TECTONIC CONTROLS ON FLUVIAL LANDSCAPE DEVELOPMENT IN CENTRAL-EASTERN PORTUGAL: INSIGHTS FROM LONG PROFILE TRIBUTARY STREAM ANALYSES - Martins, António (2016)
This study examines the long profiles of tributaries of the Tejo (Tagus) and Zêzere rivers in central eastern Portugal (West Iberia) in order to provide new insights into the patterns, timing and controls on drainage development during the Pleistocene to Holocene incision stage. The long profiles were extracted from lower order tributary streams associated with the trunk drainage of the Tejo River and one main tributary, the Zêzere River (Fig. 1). These streams flow through a landscape strongly influenced by variations in bedrock lithology (mainly granites and metasediments), fault structures delimiting crustal blocks with distinct uplift rates, and a base-level lowering history (tectonic uplift / eustatic). The long profiles of the tributaries of the Tejo and Zêzere rivers record a series of transient and permanent knickpoints. The permanent knickpoints have direct correlation with the bedrock strength, corresponding to the outcropping of very hard quartzites or to the transition from softer (slates/metagreywaques) to harder (granite) basement. The analyzed streams/rivers record also an older transient knickpoint/knickzone separating: a) an upstream relict graded profile, with lower steepness and higher concavity, that reflects a long period of quasi-equilibrium conditions reached after the beginning of the incision stage; and b) a downstream reach displaying a rejuvenated long profile, with steeper gradient and lower concavity, particularly for the final segment, which is often convex (Fig. 2). The rejuvenated reaches testify the upstream propagation of several incision waves that are the response of each stream to continuous or increasing crustal uplift and dominant periods of base-level lowering by the trunk drainages, coeval of low sea level conditions. The long profiles and their morphological configurations enabled spatial and relative temporal patterns of incision to be quantified for each individual tributary stream. The incision values of streams flowing in uplifted blocks of the Portuguese Central Range (PCR) (ca.380-280 m) indicate differential uplift and are higher than the incision values of streams flowing on the adjacent South Portugal planation surface – the Meseta (ca. 200 m). The normalized steepness index, calculated using the method of Wobus et al. (2006), proved to be sensitive to active tectonics, as lower ksn values were found in relict graded profiles of streams located in less uplifted blocks, (e.g. Sertã stream in the PCR), or in those flowing through tectonic depressions. Fig. 1 – Geological map of the study area. 1 – fluvial terraces (Pleistocene); 2 – sedimentary cover (Paleogene and Neogene); 3 – slates and metasandstones (Devonian); 4 – slates and quartzites (Silurian); 5 – quartzites (Ordovician); 6 – slates and metagreywackes (Precambrian to Cambrian); 7 – slates, metagreywackes and limestones (Precambrian); 8 – granites and ortogneisses; 9 – diorites and gabros; 10 - fault. SFf – Sobreira Formosa fault; Sf – Sertã fault; Pf – Ponsul fault; Gf – Grade fault. The differential uplift indicated by the distribution of the ksn values and by the fluvial incision was likely accumulated on a few major faults, as the Sobreira Formosa fault (SFf), thus corroborating the tectonic activity of these faults. Due to the fact that the relict graded profiles can be correlated with other geomorphic references documented in the study area, namely the T1 terrace of the Tagus River (with an age of ca. 1 Myr), the following incision rates can be estimated: a) for the studied streams located in uplifted blocks of the PCR, 0.38 m/kyr to 0.28 m/kyr; b) for the streams flowing on the South Portugal planation surface, 0.20 m/kyr. The differential uplift inferred between crustal blocks in the study area corroborates the neotectonic activity of the bordering faults, which has been proposed in previous studies based upon less robust data. Fig. 2 – Longitudinal profile of the Nisa stream a tributary of the Tejo River. Note the equilibrium relict profile upstream the older transient knickpoint (hatched line) and the downstream rejuvenated profile (continuous line). Legend: tKP – transient knickpoint; rKp – resistant knickpoint; Mt – schist and phyllite; Gr – granite; Hf – hornfels; Og – orthogneisse. In the inset Distance – Slope plots, fill circles correspond to the relict graded profile, crosses correspond to the rejuvenated profile located downstream the older transient knickpoint (tKP).